High-dimensional orbital angular momentum entanglement from an ultrathin nonlinear film - Dai, Fan; Huang, Shuang-Yin; Wang, Min; Tu, Chenghou; Li, Yongnan; Wang, Hui-Tian (Frontiers in Physics, 2022)
Entanglement, as a crucial feature of quantum systems, is essential for various applications of quantum technologies. High-dimensional entanglement has the potential to encode arbitrary large amount of information and enhance robustness against eavesdropping and quantum cloning. The orbital angular momentum (OAM) entanglement can achieve the high-dimensional entanglement nearly for free stems due to its discrete and theoretically infinite-dimensional Hilbert space. A stringent limitation, however, is that the phase-matching condition limits the entanglement dimension because the coincidence rate decreases significantly for high-order modes. Here we demonstrate relatively flat high-dimensional OAM entanglement based on a spontaneous parametric down conversion (SPDC) from an ultrathin nonlinear lithium niobite crystal. The difference of coincidences between the different-order OAM modes significantly decreases. To further enhance the nonlinear process, this microscale SPDC source will provide a promising and integrated method to generate optimal high-dimensional OAM entanglement.